2005
DOI: 10.2527/2005.83112527x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the ideal ratio of true ileal digestible sulfur amino acids:lysine in 8- to 26-kg nursery pigs1,2

Abstract: Four experiments were conducted to determine the ideal ratio of true ileal digestible (TID) sulfur AA to Lys (SAA:LYS) in nursery pigs at two different BW ranges using both DL-Met and 2-hydroxy-4-(methylthio)-butanoic acid (HMTBA) as Met sources. In Exp. 1, 1,549 nursery pigs (Triumph 4 x PIC Camborough 22; initial BW 8.3 +/- 0.08 kg) were allotted to one of nine dietary treatments. The basal diet (Diet 1) was a semicomplex corn-soybean meal-based diet (1.32% TID Lys) with no supplemental HMTBA or DL-Met (47.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
4
25
0
1
Order By: Relevance
“…Therefore, Met and TSAA concentrations in the basal diet were by 10 and 8% lower, respectively, than recommendations of NRC (1998) ( Table 2). The TSAA : Lys ratio in the supplemented diets was 60% which is in accordance with the recommendation of Gaines et al (2005).…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, Met and TSAA concentrations in the basal diet were by 10 and 8% lower, respectively, than recommendations of NRC (1998) ( Table 2). The TSAA : Lys ratio in the supplemented diets was 60% which is in accordance with the recommendation of Gaines et al (2005).…”
Section: Methodssupporting
confidence: 85%
“…Synthetic Met is often added to diets for young pigs. In corn-soybean based diets, synthetic Met is not commonly used in the growing and finishing periods but this synthetic amino acid may be added to diets for young pigs (Gaines et al 2005;Bauchart-Thevret et al 2009). In terms of amino acids supplementation, however, the feeding value of broken rice is rela-doi: 10.17221/8077-CJAS tive to corn.…”
Section: Introductionmentioning
confidence: 99%
“…Gaines et al [26,30] found a slightly higher ratio of 57 to 61% depending on the response criteria and method of assessing the breakpoint with 8 to 26 kg pigs. Yi et al [31] found a similar TSAA:lysine ratio of 58% for optimal ADG of 12 to 24 kg pigs.…”
Section: Tsaa:lysine Ratiomentioning
confidence: 99%
“…Kim and Easter (2001) and Gaines et al (2005) reported that the inclusion of fi sh meal in the diet improved piglet growth, and Mahan (1993) and Nessmith et al (1997) reported that the inclusion of 7.5% dried whey increased feed intake and growth rate in early weaned pigs. However, in the current trial, pigs had similar ADG and G:F from d 0 to 21 of the experiment when fed the HQ than when fed the LQ Phase I diets, confi rming the suggestion of Goodband et al (2006) and indicating that the digestive capacity of pigs after 40 to 45 d of age (approximately 11 to 12 kg BW) was large, and that there was no need of including greater amounts of high-quality ingredients in these diets.…”
Section: Crude Protein Content and Ingredient Complexity Of The Phasementioning
confidence: 99%